Photochemical efficiency in cladodes of ‘Gigante’ cactus pear cultivated under different spacings and organic fertilization - Cleiton F. B. Brito; Sérgio L. R. Donato; Alessandro de M. Arantes; Paulo E. R. Donato; João A. da Silva (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The objective of this study was to determine the photochemical efficiency of ‘Gigante’ cactus pear cultivated under different spacings and bovine manure doses in the semi-arid region. The experiment was conducted in a randomized block design in a 4 x 3 x 7 factorial scheme, with three replicates. The first factor consisted of four doses of organic fertilization (0, 30, 60 and 90 Mg ha-1 year-1 of bovine manure), the second one, of three spacings (1.0 x 0.5, 2.0 x 0.25 and 3.0 x 1.0 x 0.25 m) and the third one of seven reading times (6, 8, 10, 12, 14, 16 and 18 h). Chlorophyll a fluorescence readings were taken in cactus pear cladodes in the dry and rainy seasons using a pulse-modulated fluorometer. Cladodes of ‘Gigante’ cactus pear cultivated under different spacings and bovine manure doses undergo changes in photosystem II during the dry season under the physiographic conditions of the semi-arid region in Bahia. During the rainy season in the semi-arid region, the photosynthetic yield in cactus pear cladodes is considered ideal.